2011
DOI: 10.3763/ijas.2010.0545
|View full text |Cite
|
Sign up to set email alerts
|

Quncho: the first popular tef variety in Ethiopia

Abstract: Tef, Eragrostis tef (Zucc.) Trotter, is the main Ethiopian cereal grown on 2.5 million ha annually, and serving as a staple food grain for more than 50 million people. The major constraints in tef husbandry are low productivity (average about 1 t ha 21 ) and lodging. Scientific research on tef began in the late 1950s and over the years a number of improved varieties and management practices have been developed. However, the research outputs have, until recently, been little adopted by farmers. This paper gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 12 publications
0
52
0
5
Order By: Relevance
“…It is grown on 8.5Mha, yet yields are only on average 1t ha 21 . The Debre Zeit Agricultural Research Centre developed a new variety, Quncho, through participatory varietal selection, participatory plant breeding and on-farm seed multiplication and then worked with farmers' cooperatives, seed grower associations, and networks of processors and NGOs (Assefa et al, 2011). This infrastructure created effective conditions for extension of the Quncho variety, which was extended from 150 to 50,000ha over four years (to 2009).…”
Section: Crop Varietal Improvementsmentioning
confidence: 99%
“…It is grown on 8.5Mha, yet yields are only on average 1t ha 21 . The Debre Zeit Agricultural Research Centre developed a new variety, Quncho, through participatory varietal selection, participatory plant breeding and on-farm seed multiplication and then worked with farmers' cooperatives, seed grower associations, and networks of processors and NGOs (Assefa et al, 2011). This infrastructure created effective conditions for extension of the Quncho variety, which was extended from 150 to 50,000ha over four years (to 2009).…”
Section: Crop Varietal Improvementsmentioning
confidence: 99%
“…It has its own recommended rates of chemical fertilizer, seed and management practices (such as plouing frequency, weed control, post-harvest activities among others). However, there is little adoption rate by farmers and have brought Science Publications AJAS few impact on teff production (Assefa et al, 2011b). In addition, despite teff's great significance to Ethiopians, its average yield has remained low (1.3 t/ha) and supply has not kept pace with demand.…”
Section: Motivation For Efficiency Analysis Of Teff Production In Ethmentioning
confidence: 99%
“…The popular teff variety in general in Ethiopia and particularly in the study area is called Quncho. According to Assefa et al (2011b) and Fufa et al (2011) Quncho was developed from an intra-specific hybridization between two improved pure line selection varieties . However, the role of improved teff seed is not over emphasized due to short comings in seed quality and timeliness of delivery that have been long standing issues in Ethiopia.…”
Section: Factors Influencing Technical Efficiencymentioning
confidence: 99%
“…Research by Behailu (2014) in Minjar-shenkora wereda reported that row planting resulted in better teff yield than broadcasting. Repeated weeding is often required during the growing period (Assefa et al, 2011). Harvesting is generally done in with ordinary sickles and straw is separated from the grain after it has been threshed into the ground with cattle.…”
Section: Teff (Eragrostis Teff)mentioning
confidence: 99%